18F-fluciclovine-PET/CT imaging versus conventional imaging alone to guide postprostatectomy salvage radiotherapy for prostate cancer (EMPIRE-1): a single centre, open-label, phase 2/3 randomised controlled trial. Issue 10288 (22nd May 2021) - Jani, Ashesh B; Schreibmann, Eduard; Goyal, Subir; Halkar, Raghuveer; Hershatter, Bruce; Rossi, Peter J; Shelton, Joseph W; Patel, Pretesh R; Xu, Karen M; Goodman, Mark; Master, Viraj A; Joshi, Shreyas S; et al.
Summary: Background: Molecular imaging is increasingly used to guide treatment decisions and planning in prostate cancer. We aimed to evaluate the role of 18 F-fluciclovine-PET/CT in improving cancer control compared with conventional imaging (bone scan and either CT or MRI) alone for salvage postprostatectomy radiotherapy. Methods: In EMPIRE-1, a single-centre, open-label, phase 2/3 randomised controlled trial, patients with prostate cancer with detectable PSA after prostatectomy and negative conventional imaging (no extrapelvic or bone findings) were randomly assigned in a 1:1 ratio to radiotherapy directed by conventional imaging alone or to conventional imaging plus 18 F-fluciclovine-PET/CT. Computer-generated randomisation was stratified by PSA concentration, adverse pathology indicators, and androgen deprivation therapy intent. In the 18 F-fluciclovine-PET/CT group, radiotherapy decisions were rigidly determined by PET findings, which were also used for target delineation. The primary endpoint was 3 year event-free survival, with events defined as biochemical or clinical recurrence or progression, or initiation of systemic therapy, using univariate and multivariable analyses in patients who received radiotherapy. This trial is registered with ClinicalTrials.gov, NCT01666808 and is closed to new participants. Findings: From Sept 18, 2012, to March 4, 2019, 165 patients were randomly assigned, with median follow-up of 3·52 years (95% CI 2·98–3·95). PET findings resulted in four patients in the 18 F-fluciclovine-PET/CT group having radiotherapy aborted; these patients were excluded from survival analyses. Median survival was not reached (95% CI 35·2–not reached; 33% of 81 patients had events) in the conventional imaging group compared with not reached (95% CI not reached–not reached; 20% of 76 patients) in the 18 F-fluciclovine-PET/CT group, and 3 year event-free survival was 63·0% (95% CI 49·2–74·0) in the conventional imaging group versus 75·5% (95% CI 62·5–84·6) for 18 F-fluciclovine-PET/CT (difference 12·5; 95% CI 4·3–20·8; p=0·0028). In adjusted analyses, study group (hazard ratio 2·04 [95% CI 1·06–3·93], p=0·0327) was significantly associated with event-free survival. Toxicity was similar in both study groups, with the most common adverse events being late urinary frequency or urgency (37 [46%] of 81 patients in the conventional imaging group and 31 [41%] of 76 in the PET group), and acute diarrhoea (11 [14%] in the conventional imaging group and 16 [21%] in the PET group). Interpretation: Inclusion of 18 F-fluciclovine-PET into postprostatectomy radiotherapy decision making and planning significantly improved survival free from biochemical recurrence or persistence. Integration of novel PET radiotracers into radiotherapy decisions and planning for prostate cancer patients warrants further study. Funding: National Institutes of Health/National Cancer Institute, Blue Earth Diagnostics, and Winship Cancer Institute of Emory University.